(3gOGjI GdeTZhd dSjQI GdQShds - (3EHQGgje Hf eMeO Hf YHO GdQMef GdShgGFj GdeGdcj GdCRgQj,J (B1080 (3g` s ((3eMeO Hf eMeO Gdecfi HCHi SGde GdTQHjfi s)
(3ChdgG (B:s
(3MeOkG def fVQ hLhg Cgd GdMOjK , hUdGI hSdGekG Ydi ef fRd Ydjg GdMOjK s
(3fbdkG Yf fSNI GdeDdas
(3dNU ajg GdSjQI GdMdHjIs
(3fSHJg Edi ShgG ef ENeje eUQs
(3hQJHg Ydi KeGfjI hYTQjf HGHkG hNGJeI ajgG CMO YTQ ebUOkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B96s
Keywords: (3GdJGQjNs